ZAKAT DISTRIBUTION: AN INDIVIDUALIZED APPROACH BASED ON MAQASHID AL-SYARIAH - Laily Hidayati Rosyidi; Azy Athollah Yazid; Sri Wahyunita (Journal of Economic Perspectives and Business Innovation, 2025)
AbstractZakat distribution is a central instrument in Islamic social finance aimed at achieving justice and social welfare. This study proposes an individualized approach to zakat distribution based on the framework of Maqashid al-Shariah, which emphasizes the protection of religion, life, intellect, lineage, and wealth. Using a qualitative normative method, the research analyzes classical Islamic jurisprudence, contemporary zakat management practices, and socio-economic needs of beneficiaries. The findings suggest that a needs-based, individualized model of distribution allows zakat institutions to allocate funds more effectively by considering the specific conditions of recipients. Such an approach enhances poverty alleviation, promotes human development, and ensures that zakat fulfills its broader ethical objectives. The study concludes that integrating Maqashid al-Shariah into modern zakat governance can strengthen accountability, social impact, and long-term community empowerment. Keywords: zakat distribution, Maqashid al-Shariah, Islamic social finance, poverty alleviation, welfare development